Architecture and the Social Sciences : Inter- and Multidisciplinary Approaches between Society and Space - Manuela Mendes, Maria; Sá, Teresa; Cabral, João (Springer International Publishing : Imprint: Springer, 2017)
This book contributes to current debates on the relationship between architecture and the social sciences, highlighting current interdisciplinary and transdisciplinary teaching as well as research and practice in architecture and urbanism. It also raises awareness about the complementarities and tensions between the spaces of the project, including the construction spaces and living space. It gives voice to recent projects and socio-territorial interventions, focusing on interdisciplinary and multidisciplinary approaches between society and space. Divided into two parts, the first part discusses the possible dialogue between social sciences and architecture, while the second part explores architecture, politics and social change in urban territories from a European perspective.
Keywords: Social sciences.; Landscape architecture.; Sociology, Urban.; Human geography.; elektronické knihy; electronic books